Heart Failure with Preserved Left Ventricular Ejection Fraction: A Complex Conundrum Simply Not Limited to Diastolic Dysfunction - Angel Lopez-Candales; Talal Asif; Khalid Sawalha; Nicholas B. Norgard (Hindawi-Wiley, 2023)
Over the last two decades, the changing paradigm of heart failure with preserved ejection fraction (HFpEF) has transformed our understanding not only of the pathophysiology of this clinical entity but also the diagnostic and therapeutic approaches aimed at treating this complex patient population. No longer HFpEF should be seen as simply left ventricular diastolic dysfunction but as a group of that in addition of having small and thick left ventricles with abnormal diastolic filling patterns as their main pathophysiologic abnormality; they also have whole host of different abnormalities. In fact, this heterogeneous clinical entity embodies numerous mechanisms and is linked to multiorgan dysfunction, with hypertension and obesity playing a major role. Although we have gained an enormous amount of understanding not only on the causes but also the downstream effects of HFpEF, there is still much to be learned before we can fully comprehend this complex clinical entity. It is the main intention of this review to synthesize the most recent attributes, mechanism, diagnostic tools, and most useful therapeutic alternatives to be considered when evaluating patients either complaining of dyspnea on exertion as well as exercise intolerance or those recently admitted with HF symptoms but with normal LVEF in the absence of any other valvular abnormalities